Immunological features of the bone marrow microenvironment and assessment of bone marrow lesions in patients with classical Hodgkin lymphoma - A. A. Melnikova; F. M. Abbasbeyli; T. Yu. Mushkarina; M. A. Vernyuk; P. A. Zeynalova; L. Yu. Grivtsova; S. A. Ivanov; A. D. Kaprin (Онкогематология, 2024)
Background. The study of bone marrow involvement is a necessary step in disease staging, both in non-Hodgkin lymphomas and in the case of Hodgkin lymphoma (HL). The standard assessment of bone marrow lesion is carried out based on immunohistochemical examination of bone marrow trepanobioptate, and recently computer technologies (positron emission tomography combined with computed tomography) have been introduced to assess bone marrow involvement. At the same time, immunological methods for detecting tumor cells using multicolor flow cytometry are more available. In addition, they allow for detailed study of the tumor bone marrow microenvironment.Aim. To evaluate the immunomorphological features of bone marrow in HL and the possibility of identifying specific bone marrow lesions using flow cytometry.Materials and methods. The study included the analysis of 107 bone marrow samples. The samples were obtained from 107 patients with various variants of classical HL, diagnosed and treated at the Lapino Clinical Hospital and the P.A. Herzen Moscow State Medical Institute from 2018 to 2022.Results. The features of bone marrow lymphocytes subpopulation in patients with classical HL are shown.Conclusion. An immunological assessment of bone marrow involvement degree was carried out, data from flow cytometry and immunohistochemical examination of trephine biopsy specimens during primary diagnosis were compared, and the features of bone marrow lymphocytes subpopulation were evaluated. The interrelation of these factors at the diagnostic stage in classical variants of HL was studied. At the end of treatment, the primary immunological data (the degree of bone marrow involvement) were compared with the results of the positron emission tomography combined with computed tomography.